An experimental study of detection limits and corresponding doses of IRSN in vivo monitoring vehicles in the case of post-accident scenarios. Issue 4 (13th November 2014) - Broggio, D.; Navarro, É.; Viltard, D.; Challeton-de Vathaire, C.; Bô, R.; Debrose, L.; Moya, X.; Franck, D.
Abstract : The measurement performances of in vivo monitoring vehicles were studied considering an increase in the radiological background in areas where the population is not evacuated after a nuclear accident. The study focused on 137 Cs and 131 I Detection Limits (DLs) and corresponding doses, for adults and one-year-old children. These DLs for ground contamination were obtained experimentally using a grid of point sources. Then, the DLs and doses were calculated using the experimental data and a safety factor for two accident scenarios. For these scenarios the 137 Cs DL corresponds to a committed effective dose of 0.02 mSv. The 131 I DL corresponds to committed equivalent thyroid doses of 3 mSv (adult) and 30 mSv (one-year-old child). To guarantee a 45 mSv thyroid equivalent dose assessment for the child the surface activity of 131 I + 132 I + 133 I should be below 1.6 MBq/m 2 . This study shows that the vehicles can operate in a contaminated area where the population is not evacuated. However, in such a case, the contamination level outside and inside the vehicle should be kept stable to guarantee efficient body counting.